2012 International Symposium on Innovations in Intelligent Systems and Applications 2012
DOI: 10.1109/inista.2012.6247049
|View full text |Cite
|
Sign up to set email alerts
|

Antenna azimuth position control with classical PID and fuzzy logic controllers

Abstract: In this study, an antenna azimuth position control system is controlled by using a Proportional-IntegralDerivative (PID) controller and a fuzzy logic controller (FLC) designed in Matlab/Simulink environment. In order to obtain the best system response with FLC, different types of fuzzy rules and membership functions are tested. System responses with proposed controller and PID controller are compared to each other and commented according to these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The 2-DOF formulation of antenna azimuth position control system is shown in Fig. 1 and Table 1 shows block diagram parameters of antenna azimuth position control system [11][12]. It represents the plant dynamics and the desired closed loop system performance specifications in frequency domain.…”
Section: General Concept Of Qftmentioning
confidence: 99%
See 3 more Smart Citations
“…The 2-DOF formulation of antenna azimuth position control system is shown in Fig. 1 and Table 1 shows block diagram parameters of antenna azimuth position control system [11][12]. It represents the plant dynamics and the desired closed loop system performance specifications in frequency domain.…”
Section: General Concept Of Qftmentioning
confidence: 99%
“…For QFT controller, it is observed that actual closed loop variation is much less compared to specified closed loop variation. The time domain performances of the fixed plant , in [11][12] with respect to QFT controller is shown below in Table 2. …”
Section: F Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…An antenna azimuth position is controlled using designed proportional-integral-derivative (PID) controller and fuzzy logic controller (FLC). From the closed loop response, FLC delivers the finest closed loop response compared with PID controller [4]. The firing angle of the motor is adjusted, it drives the antenna due changing the output angle.…”
Section: Introductionmentioning
confidence: 99%